Conservation and restoration of Mexican forests in the global change scenario: a shared responsibility with multiple benefits - Badano, Ernesto I. (Instituto de Ecología, A.C., 2016)
Our planet is facing a strong change induced by human activities, which is usually referred as Global Change. Concern about the socioeconomic consequences of this phenomenon has led to several international commitments for reducing the emissions of greenhouse gasses, which were summarized in the Kyoto Protocol of the United Nations. The Protocol established a number of strategies to mitigate and reduce the atmospheric impacts of CO2 emissions, which led to the creation of the international carbon market. The extensive forested areas of Mexico may position this country in the carbon market as an important provider of environmental services. Therefore, conservation and restoration of Mexican forests can be viewed as a potential business opportunity that would contribute to the economic and social development of the country. However, reaching these goals requires the joint action of different social sectors, including governments, private companies, the scientific community and the general population. This article illustrates how this interaction can be articulated and how it can provide multiple benefits for contributing parties.